Chief Financial Officer Co-option and Chief Executive Officer Compensation - Dikolli, Shane S.; Heater, John C.; Mayew, William J.; Sethuraman, Mani (Management Science, 2021)
We study whether relative power in the chief executive officer (CEO)–chief financial officer (CFO) relationship influences CEO compensation. To operationalize relative power of a CEO over a CFO, we define CFO co-option as the appointment of a CFO after a CEO assumes office. We find that CFO co-option is associated with a CEO pay premium of about 10%, which is concentrated more in the early years of the co-opted CFO’s tenure and in components of compensation that vary with the achievement of analyst-based earnings targets. Our evidence also indicates that a primary channel through which CEO power over a co-opted CFO yields the achievement of earnings targets is the use of earnings management to inflate earnings. Co-opted CFOs rely primarily on using discretionary accruals to manage earnings prior to the Sarbanes–Oxley regulatory intervention and switch to real-activities manipulation afterward. The evidence thus suggests that the form of earnings management depends on costs imposed on the CFO to inflate earnings. This paper was accepted by Suraj Srinivasan, accounting.